Chitosan Reinforced Polyvinyl Alcohol and Nanoparticles Treatment to Promote Skin Wound Healing in Diabetes Induced Mouse Model - R. Kttafah, Huda; Hanaa S. Mahmood; N. Olewi, Hussein (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
A group of mice were captured. We divided the 3-month-old mice into groups. We limited each group to a specific type of treatment, using different components of silver (Ag) and gold (Au) in various proportions. The control group was left untreated. We stimulated her diabetes with injections of the substance alloxan, which led to the development of her condition. It was left for three days after the injection of this substance, and then the diabetes was checked with a diabetes testing device until all the required mice were infected with diabetes. Next, they removed the hair from the mouse's top and used a special tool, a ring with a diameter of 8 mm, to cut the skin. During the work, they used two types of anesthetics: ketamine and xylazine. The ketamine relaxes her muscles and causes her death, so she abandoned the xylazine and relied solely on the first type. The percentage of the anesthetic substance injected depends on its weight. Therefore, we created an incision on the mouse. Then I began treating the wounds: the first group with 100% AgNPs, the second group with 100% AuNPs, and the third group with samples of a mixture of AgNPs and AuNPs at a ratio of 50% each. The fourth and final group remained without treatment. With a weekly checkup for diabetes. The treatment entailed applying the sample to the wound and adhering it with a medical adhesive, periodically replacing it. After the second week of treatment, some of the wounds began to heal. By the end of the fourth week, it had completely healed. The group that was treated with the mixed samples had the best and fastest recovery and wound healing among the rest of the samples, followed by the mixture samples.